Indicators for benchmarking in Norwegian academic libraries: Testing the usability of national collection data - Landøy, Ane; Raade, Johanne (Qualitative and Quantitative Methods in Libraries, 2017)
In a world of rapid changes, there is a need for leadership and strategic planning based on statistical evidence - evidence based leadership. In Norway, the National Library has led the way in developing indicators for the public and the academic libraries, and these indicators may be used either longitudinally or for benchmarking within or between libraries. In this paper, the authors will give examples of the use of indicators for the usage of the university library holdings, through the traditional measurements of loans, as well as statistics on down loads of electronic books.